Teaching Metaphysics – Death as a Way Into Metaphysics - Biondić, Marin (Od filozofije poučevanja do poučevanja filozofije: Festschrift Rudi Kotnik, 2025)
We can teach some classical metaphysical themes indirectly, through a field in which different metaphysical themes intersect. In that way, something that can be too abstract for young minds, if we put it in some context, can be very concrete and open for understanding and investigation. In this article, I will try to show what starting point for metaphysics is the death; how common-sense questions transfer into metaphysical questions; and how metaphysical theories determine our pre-philosophical attitudes. I will take three metaphysical fields – personal identity, nature of harm, and philosophy of time – and show how students deal with them through the discussion of the value of death for the person who dies. The main point is that students should see, and they actually do see, that there is no way to avoid hard metaphysical questions if they want to think of things which, at first sight, can seem clear, undoubtful, and commonsensical – but they are not.